Recruiting Intensity during and after the Great Recession: National and Industry Evidence - Davis, Steven J; Faberman, R. Jason; Haltiwanger, John C (American Economic Review, 2012)
We measure job-filling rates and recruiting intensity per vacancy at the national and industry levels from January 2001 to September 2011 using data from the Job Openings and Labor Turnover Survey. Industry-level movements in these variables are at odds with implications of the standard matching function in labor search theory but consistent with a generalized function that incorporates an important role for recruiting intensity. Construction makes up less than five percent of employment but accounts for more than 40 percent of the large swings in the job-filling rate during and after the Great Recession.